Ecobiomorphology of ruderal plants meeting in Karaganda city environment - Kyzdarova, D.K.; Mussina, R.T. (Fundamental and Experimental Biology, 2017)
This article represents to determine the species of weeds in Central Kazakhstan, especially in Karaganda region, and to give ecobiomorphological description of them. In addition, it was examined how to collect and dry the weeds in dry sections of Central Kazakhstan, to determine the type, the form of life, the period of vegetation of collected plants and to tell about the ecological significance in water and dry regions. By classifying the economic significance of weeds not only harmful effects, but also the benefits were described such as in medicine, in livestock food agriculture, food and in other industries. As a result of our research in the vicinity of the city of Karaganda collected 75 species, and provides systematic information weeds. They are classified into 20 families and 65 genera. Most weeds are members of the following families: Asteraceae, Cruciferae, Fabaceae, Poaceae, Boraginaceae; Chenopodiaceae, Umbelliferae, Labiatae; Solanaceae; Rosaceae; Amaranthaceae, Cuscutaceae, Plantaginaceae; Euphorbiaceae, Caryohyllaceae, Malvaceae, Polygonaceae, Convolvulaceae.